Papillary Thyroid Carcinoma in a Branchial Cleft Cyst without a Thyroid Primary: Navigating a Diagnostic Dilemma - Douglas S. Ruhl; Mark F. Sheridan; Joseph C. Sniezek (Case Reports in Otolaryngology)
We report a rare case of papillary thyroid carcinoma incidentally found within a branchial cleft cyst. Only four other cases have been described in the literature. A total thyroidectomy and selective neck dissection was performed, and no evidence of occult primary disease was found after review of fine sections. Branchial cleft cysts are the most common lateral neck masses. Ectopic thyroid tissue within a branchial cleft cyst is an unusual phenomenon, and papillary thyroid carcinoma arising from this tissue is extremely rare. Clinicians are left with a diagnostic dilemma when presented with thyroid tissue neoplasm within a neck cyst in the absence of a thyroid primary—is this a case of metastatic disease with a missed primary or rather carcinoma arising in ectopic thyroid tissue? A thorough discussion of the etiologies of these lateral neck masses is reviewed including the embryogenesis of thyroid tissue in a branchial cleft cyst. The prognosis of patients with papillary thyroid carcinoma in lateral neck cysts without a primary site identified appears to be good following excision of the cyst and total thyroidectomy. Other management recommendations regarding these unique lateral neck malignancies are also presented.